The Effects of Parent-Child Interactive Music Therapy on Sentence Verbalisation in a Child with Autism Spectrum Disorder: A Case Study - Chanyanit, Charoenphol; Chiengchana, Natee; Tayrattanachai, Nion (Malaysian Journal of Music, 2019)
This study examined the effects of parent-child interactive music therapy on sentence verbalisation in a child with Autism Spectrum Disorder (ASD) and was conducted via a case study design. The participants were a boy with autism spectrum disorder and his mother. The child and his mother attended interactive music therapy sessions that provided singing, instrument playing, songwriting, and movement. Twelve sessions were conducted during this study consisting of two initial assessments and 10 intervention sessions. The initial assessments determined the child’s behaviour while in an environment with music and his preferred music. The intervention sessions consisted of two parts to enhance the child’s sentence verbalisation. The first part aimed to teach and assess words through pre-composed songs. The second part aimed to motivate the child’s sentence verbalisation using one selected song and measured the verbalisation score using a verbalisation rating scale. The results showed the effectiveness of parent-child interaction on the child’s ability to focus on verbalisation through a combination of singing and movement activities. The child’s verbalisation was clearer and more accurate after attending singing activities with his mother as she held the child in her arms and together engaged in physical interaction. His average verbalisation score increased from 1.33 to 3, presenting an improvement of his verbalisation from verbalising single words to verbalising three-word sentences that included a subject, verb, and object.